Calculation of the three-dimensional structure of the membrane-bound portion of melittin from its amino acid sequence. - Pincus, M R (1982)
The structure of the NH2-terminal, 20-residue membrane-bound portion of melittin has been computed with empirical energies (ECEPP, Empirical Conformational Energy Program for Peptides). First, a search was made for long stretches of nonpolar residues. Then, the low-energy conformations of these segments were built up by combining successively the low-energy conformations of their component di- and tripeptides. The minimum-energy conformations of each of these component peptides used in this buildup process were selected so that each had a distinct backbone conformation; these distinct backbone conformations were designated as nondegenerate minima. Structured segments (i.e., those with only a few low-energy conformations) resulting from this process were identified and used as nucleation sites for building up larger structures by adding adjacent peptide segments. At each stage, the energy of each structure was minimized. Only two low-energy structures were found, both of which were alpha-helical from Gly-1 to Thr-10 and from Pro-14 to Ile-20. In one of them, the first helix continues through Thr-11-Gly-12; in the other, there is a bend at Thr-11-Gly-12. However, because of compensating changes in the dihedral angles, both structures are very similar. The calculated structures seem to agree well with experimental data.